2014
DOI: 10.2215/cjn.05230513
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Insulin Sensitivity and Its Association with Mortality among Men with CKD Stages 3 and 4

Abstract: Background and objectives Insulin resistance participates in the pathogenesis of multiple metabolic and cardiovascular diseases. CKD patients have impaired insulin sensitivity, but the clinical correlates and outcome associations of impaired insulin sensitivity in this vulnerable population are not well defined.Design, setting, participants, & measurements The prospective cohort study was from the third examination cycle of the Uppsala Longitudinal Study of Adult Men, a population-based survey of elderly men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 37 publications
2
47
1
Order By: Relevance
“…The data of Xu et al support the finding that insulin resistance can already be observed in early CKD stages. Insulin resistance was not directly associated with significantly increased cardiovascular mortality in patients with stages 3-4 CKD, but graded relations among physical inactivity and smoking, together with insulin resistance, were identified as a deleterious combination for increased mortality (19). Interestingly, in line with other observations, the presence of insulin resistance was independent of overweight-a major risk factor in the classic metabolic syndrome (8,9).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The data of Xu et al support the finding that insulin resistance can already be observed in early CKD stages. Insulin resistance was not directly associated with significantly increased cardiovascular mortality in patients with stages 3-4 CKD, but graded relations among physical inactivity and smoking, together with insulin resistance, were identified as a deleterious combination for increased mortality (19). Interestingly, in line with other observations, the presence of insulin resistance was independent of overweight-a major risk factor in the classic metabolic syndrome (8,9).…”
supporting
confidence: 63%
“…The inclusion criterion for analysis was an eGFR of 20-60 ml/min per 1.73 m 2 calculated on the basis of serum cystatin C concentrations. Exclusion criteria were incomplete data and preexisting diabetes (19). Definite strengths of the study were the use of serum cystatin C to estimate GFR in an elderly population and the assessment of insulin resistance by the euglycemic clamp technique.…”
mentioning
confidence: 99%
“…Insulin resistance in both CKD and normal mice were prevented by antioxidant superoxide dismutase (SOD)/catalase mimetic treatment; however potential confounders such as urea-induced intestinal inflammation and hepatic recycling of the infused urea were not addressed. Overall, these experiments suggest that urea-induced insulin resistance may contribute to the high rates of impaired glucose homoeostasis observed in the CKD population [76,77] but the clinical significance remains to be confirmed via human trials.…”
Section: Insulin Resistancementioning
confidence: 88%
“…Nevertheless, in agreement with community reports (26,27), our multivariate analysis showed that the presence of diabetes mellitus (or insulin resistance) and the concentrations of triglycerides were the main independent determinants of NEFA variance in our CKD population. Both diabetes and hypertriglyceridemia have been associated with increased CVD risk in patients with CKD (28)(29)(30), but the association between insulin resistance and CVD risk in nondiabetic CKD is less conclusive (31,32).…”
Section: Discussionmentioning
confidence: 99%